Estudo da oxidação parcial do metano a gás de síntese usando catalisadores de platina suportada - Napolitano, Marcos Nogueira (2005)
Catalysts containing 1.5% (wt) of Pt supported in Nb2O5, LaCoO3, ZrO2, CeZrO2 e CeZrO2-M mesoporous were prepared and characterized using the following techniques: temperatura programmed reduction (TPR), x-ray diffraction (XRD) and temperatura programmed desorption of CO2 e CO chemisorbed at room temperatura after reduction at 500°C under H2 flow. The catalysts were analyzed by partial oxidation and reforming of methane reactions with CO2 and H2O, at same temperatura (800°C), pression (1 atm) and space velocity (180000 h’1). The results showed that the magnitude of conversion of methane during partial oxidation reaction decreased in the following order: Pt/CeZrO2 > Pt/CeZrO2-M > Pt/ZrO2 > Pt/LaCoO3 > Pt/Nb2O5 s 0. Such results were in accordance with the evolution of existing redox/basic sites and with the balance between these sites and metallic interfàcial sites. Reducibility of the catalysts follows the same order, except for Pt/LaCoO3, which was more reducible than Pt/ZrO2. A triangular scheme of mechanism, where direct and indirect steps of synthesis gas formation coexist, explains all the existing results, either modifying reactional condition or changing employed catalyst. The result of reforming of methane with CO2 and H2O revealed the following increasing order of activity: Pt/CeZrO2-M > Pt/CeZrO2 > Pt/ZrO2 »> Pt/LaCoO3 s Pt/Nb2C>5 = 0. They are coherent with the bifunctional mechanism, where the balance between metallic and redox sites was of key importance to obtain synthesis gas in a ratio H2/CO = 2, as in partial oxidation.